2020
DOI: 10.1002/aoc.5687
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in anticancer ruthenium Schiff base complexes

Abstract: Nowadays in cancer treatment, both metal complexes and organic molecules are being widely used. Current years have seen a surge of interest in the application of organometallic compounds to treat cancer and other diseases. Undeniably, the unique properties of organometallic compounds, intermediate between those of classical inorganic and organic materials, provide new opportunities in the field of medicinal chemistry. Since the discovery of cisplatin, many transition metal complexes have been synthesized and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 89 publications
0
36
0
Order By: Relevance
“…Numerous Schiff-bases and their derivatives have been reported to possess promising biological properties and several review articles have been published in the past few years. [37][38][39][40][41][42][43][44] Recently, review articles regarding the biological applications of macrocyclic Schiff-base ligands and their metal complexes have been published. [32,34] However, no comprehensive review has been published recently on the biological properties of metallic derivatives of acyclic Schiff-base ligands.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous Schiff-bases and their derivatives have been reported to possess promising biological properties and several review articles have been published in the past few years. [37][38][39][40][41][42][43][44] Recently, review articles regarding the biological applications of macrocyclic Schiff-base ligands and their metal complexes have been published. [32,34] However, no comprehensive review has been published recently on the biological properties of metallic derivatives of acyclic Schiff-base ligands.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…[34] Macrocyclic Schiff-bases [32][33][34] have found important applications in macrocyclic and supramolecular chemistry, and various heterocyclic Schiff-bases and their derivatives play crucial roles in medicinal chemistry. [35,36] Furthermore, depend-to their structural flexibility, they can be synthetically modified and fine-tuned for specific biological applications and many metallic [3,15,17,18,[37][38][39] and non-metallic [15,[40][41][42][43][44] derivatives of Schiffbases are being researched extensively to develop new compounds with desired biological properties. The imine or azomethine group in structure-activity relationship (SAR) studies of Schiff-bases have shown the considerable chemical and biological importance for the lone pair of electrons in the sp 2 -hybridized orbital of nitrogen atom of the À C=NÀ group.…”
Section: Introduction 1schiff-bases and Their Different Derivativesmentioning
confidence: 99%
“…Over the past few decades, transition metal-based compounds have been extensively used in the anticancer medicinal chemistry area [ 12 , 13 , 14 , 15 ]. Platinum (Pt)-based medications such as cisplatin (CIS) and its analogs carboplatin (CAR) and oxaliplatin (OXA) ( Figure 1 ) have been used worldwide in cancer treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relatively easy synthesis of a wide range of Schiff bases makes them versatile ligands and consequently they have found widespread use in many areas including organometallic chemistry (Kargar et al, 2020), polymer synthesis (Mighani, 2020), anticancer drugs (Parveen, 2020), catalysts (Kumari et al, 2019) and sensors (Sahu et al, 2020). In addition, Schiff bases themselves have been found to display interesting properties with anils, Schiff bases of salicylaldehyde derivatives with aniline derivatives, having been found to exhibit both thermo-and photochromism in the solid-state (Senier & Shepheard, 1909;Cohen & Schmidt, 1962;Cohen et al, 1964).…”
Section: Introductionmentioning
confidence: 99%